PENGARUH KUALITAS PELAYANAN, PROMOSI SOSIAL MEDIA DAN LOKASI TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA BENGKEL PROJECT GARAGE DI SITUBONDO - Muhamad Zitkul Aziz; Lita Permata Sari; Lusiana Tulhusnah (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study analyzes the influence of service quality, social media promotion, and location on purchasing decisions and consumer satisfaction at the Project Garage Workshop, with purchasing decisions as an intervening variable. A quantitative research method was applied using path analysis to test the hypotheses. The research results prove that location is a key factor with a significant and positive influence, both directly on purchasing decisions and indirectly on consumer satisfaction, mediated by purchasing decisions. This finding is consistent with previous research that emphasizes the strategic role of location in the service industry. Meanwhile, social media promotion only proved to have a significant direct effect on customer satisfaction, indicating that while social media is effective in building engagement, its effectiveness in driving purchasing decisions is still limited. Meanwhile, service quality did not show a significant direct or indirect effect, indicating that consumers perceive the service provided as industry standard and therefore not a key differentiator. These findings conclude that purchasing decisions significantly influence customer satisfaction, and that Project Garage customers prioritize location factors and practical considerations such as price and waiting area comfort over service quality and social media promotion. The managerial implications of this study emphasize the importance of maintaining the advantage of location accessibility, optimizing more targeted digital marketing strategies, and enhancing other supporting elements such as the workshop's physical comfort and competitive pricing to build customer satisfaction holistically and sustainably.